Investigating Plastic-Degrading Potential of Environmental Microbes in Polluted Ecosystems (International Journal of Scientific Research in Science and Technology, 2025)
Polyethylene’s extreme non-biodegradability has made it a major environmental contaminant, and numerous researchers are working to find a means to break it down. Here, we’ve attempted to use soil bacteria that were isolated from plastic disposal sites to break down plastic in this research. Polystyrene (PS), Polyethylene terephthalate (PET), High-density polyethylene (HDPE), and Low-density polyethylene (LDPE) are common plastic polymers that provide serious environmental problems because they don’t break down naturally. Soil samples from plastic disposal sites in Mohali, Chandigarh, and Hoshiarpur were examined in this study to look for microbes that could break down the plastics. Bacteria were isolated after a series of transfers using carbon-free basal media (CFBM) enhanced with plastic pieces. Through morphological and biochemical characterization, three strains of Gram-positive bacteria were identified: Propionibacterium acnes, Staphylococcus sp., and Paenibacillus sp. By measuring weight loss over a five-month period, biodegradation experiments revealed that P. acnes showed no degradation, Staphylococcus sp. achieved 24% degradation (from 50 mg to 42 mg), and Paenibacillus sp. destroyed LDPE by 16%. These results support earlier research showing that Paenibacillus and Staphylococcus have the ability to degrade plastic, and they demonstrate that P. acnes does not degrade polymers despite its ability to build biofilms. The outcomes validate the possible use of these bacterial isolates in plastic waste management based on biodegradation.